Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Holland Bakery Lampung Tengah - Novalinda, Anisa Ade; Sari, Debi Delvia (Jurnal Manajemen Bisnis dan Keuangan, 2022)
Price is the number of money consumers needs to obtain products or services to meet their needs. A product is said to be of high quality if it is judged to carry out its functions properly and better than other similar products. The quality of a product is seen in its durability, reliability, accuracy, and ease of maintenance. Consumer purchasing decisions are some considerations that consumers realize by buying the product. This study aims to determine the effect of price and product quality on purchasing decisions at Holland Bakery Central Lampung. The population of this study were all residents of Central Lampung who had bought Holland Bakery products in Central Lampung. The number of samples for data collection is 54 respondents who have bought products from Holland Bakery. The method of data collection is the distribution of questionnaires and documentation. Analysis of the data from this study is quantitative analysis with the SmartPLS application and multiple linear regression analysis tools. The results of the study Price and product quality have a positive and significant influence on customer buying interest at Holland Bakery Central Lampung.